A rapid and sustained improvement of calcification propensity score (serum T50) after successful kidney transplantation: Reanalysis of a randomized controlled trial of ibandronate. Issue 12 (26th October 2017) - Smerud, Knut T.; Åsberg, Anders; Kile, Håkon; Pasch, Andreas; Dahle, Dag O.; Bollerslev, Jens; Godang, Kristin; Hartmann, Anders
Abstract: A serum test called T50 assesses the overall propensity for calcification of the blood and is associated with cardiovascular outcomes. We aimed to examine T50 over time in kidney transplant recipients and also address any effects of ibandronate. Serum samples taken from kidney transplant patients included in a prospective, randomized placebo controlled study of ibandronate were analyzed in retrospect. Adequate analyses were performed at baseline (approximately 3 weeks after transplantation) in 129 patients, at 10 weeks in 127 patients and at 1 year in 123 patients. There were no statistical differences between ibandronate and placebo treatment in terms of T50 at 10 weeks ( P  = .094) or at 1 year ( P  = .116). Baseline T50 was a significant covariate ( P  < .0001) for T50 scores at 10 weeks and 1 year. In the total cohort, there was a highly significant ( P  < .0001) increase in T50 of 26.6% after 10 weeks and T50 remained stable after 1 year. T50 change was inversely correlated to phosphate of −0.515 ( P  < .0001) and to change in serum albumin ( P  < .03). We found that T50 increased from baseline to 10 weeks after transplantation with no further change after 1 year. Ibandronate had no effect on T50 .